Differences in the Fatty Acid Profile, Morphology, and Tetraacetylphytosphingosine-Forming Capability Between Wild-Type and Mutant Wickerhamomyces ciferrii - Choi, Jun Young; Hwang, Hee Jin; Cho, Woo Yeon; Choi, Jong-il; Lee, Pyung Cheon (Frontiers in Bioengineering and Biotechnology, 2021)
One tetraacetylphytosphingosine (TAPS)-producing Wickerhamomyces ciferrii mutant was obtained by exposing wild-type W. ciferrii to γ-ray irradiation. The mutant named 736 produced up to 9.1 g/L of TAPS (218.7 mg-TAPS/g-DCW) during batch fermentation in comparison with 1.7 g/L of TAPS (52.2 mg-TAPS/g-DCW) for the wild type. The highest production, 17.7 g/L of TAPS (259.6 mg-TAPS/g-DCW), was obtained during fed-batch fermentation by mutant 736. Fatty acid (FA) analysis revealed an altered cellular FA profile of mutant 736: decrease in C16:0 and C16:1 FA levels, and increase in C18:1 and C18:2 FA levels. Although a significant change in the cellular FA profile was observed, scanning electron micrographs showed that morphology of wild-type and mutant 736 cells was similar. Genetic alteration analysis of eight TAPS biosynthesis-related genes revealed that there are no mutations in these genes in mutant 736; however, mRNA expression analysis indicated 30% higher mRNA expression of TCS10 among the eight genes in mutant 736 than that in the wild-type. Collectively, these results imply that the enhancement of TAPS biosynthesis in mutant 736 may be a consequence of system-level genetic and physiological alterations of a complicated metabolic network. Reverse metabolic engineering based on system-level omics analysis of mutant 736 can make the mutant more suitable for commercial production of TAPS.